FGF2 High Molecular Weight Isoforms Contribute to Osteoarthropathy in Male Mice - Meo Burt, Patience; Xiao, Liping; Dealy, Caroline; Fisher, Melanie C.; Hurley, Marja M. (Endocrinology (Philadelphia), 2016)
Humans with X-linked hypophosphatemia (XLH) and Hyp mice, the murine homolog of the disease, develop severe osteoarthropathy and the precise factors that contribute to this joint degeneration remain largely unknown. Fibroblast growth factor 2 (FGF2) is a key regulatory growth factor in osteoarthritis. Although there are multiple FGF2 isoforms the potential involvement of specific FGF2 isoforms in joint degradation has not been investigated. Mice that overexpress the high molecular weight FGF2 isoforms in bone (HMWTg mice) phenocopy Hyp mice and XLH subjects and Hyp mice overexpress the HMWFGF2 isoforms in osteoblasts and osteocytes. Given that Hyp mice and XLH subjects develop osteoarthropathies we examined whether HMWTg mice also develop knee joint degeneration at 2, 8, and 18 mo compared with VectorTg (control) mice. HMWTg mice developed spontaneous osteoarthropathy as early as age 2 mo with thinning of subchondral bone, osteophyte formation, decreased articular cartilage thickness, abnormal mineralization within the joint, increased cartilage degradative enzymes, hypertrophic markers, and angiogenesis. FGF receptors 1 and 3 and fibroblast growth factor 23 were significantly altered compared with VectorTg mice. In addition, gene expression of growth factors and cytokines including bone morphogenetic proteins, Insulin like growth factor 1, Interleukin 1 beta, as well as transcription factors Sex determining region Y box 9, hypoxia inducible factor 1, and nuclear factor kappa B subunit 1 were differentially modulated in HMWTg compared with VectorTg. This study demonstrates that overexpression of the HMW isoforms of FGF2 in bone results in catabolic activity in joint cartilage and bone that leads to osteoarthropathy.